THE TRANSFORMATION OF LOCAL VALUES AND CULTURE IN FACING GLOBALIZATION IN INDONESIA’S MULTICULTURAL SOCIETY - Asmara Juana Suhardi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Indonesia, with its vast cultural diversity and rich local traditions, faces significant challenges in maintaining its identity amid the forces of globalization. This study explores the transformation of local values and cultural practices as Indonesia’s multicultural society interacts with global influences. Through qualitative research, including interviews and ethnographic observations, the study examines how globalization impacts local customs, languages, religious practices, and social norms across different ethnic groups in Indonesia. The findings reveal a complex dynamic where globalization both threatens the preservation of traditional values and simultaneously facilitates their evolution. Local communities are adopting global trends while reinterpreting them through a lens of their cultural heritage. Furthermore, globalization has led to the blending of traditional and modern cultural expressions, fostering a hybrid identity. The study also highlights the role of media, education, and migration in accelerating this transformation. This research provides valuable insights into how multicultural societies like Indonesia negotiate the delicate balance between cultural preservation and global integration, contributing to the broader discourse on globalization's impact on local cultures.